HUBUNGAN SPIRITUALITAS DENGAN STRES LANSIA DI PUSKESMAS PAKJO PALEMBANG - Dheni Koerniawan; Uci Candrawulan (Elisabeth Health Jurnal, 2018)
Elderly in aging process experienced physiological decline and loss and grieving. This can make elderly vulnerable to stress. Stress can make elderly not productive and focus on his/her losing. Stress might causes loss of interest, feelings of failure, and restless in physically and emotionally. Stress can impact to anger, anxiety, depression, pathological symptoms, and psychiatric illness. Thus, it require effective ways to manage stress which is experienced by older adults. Nursing management in handling stress can be done with holistic approach which one is spiritual care. Strong belief can make powerful positive effect to mind and body and can bring comfort. Goals : This study aim to know the relationship between spirituality with stress elderly in Palembang. Methods: Survey analytic design with cross sectional approach had done to 72 respondents by purposive. Data have been taken by Religious Commitment Inventory (RCI) and Perceived Stress Scale (PSS) then analyzed by Pearson’s correlation. Results : Results showed mean of RCI 31,03 (moderate religious) with standard deviation 7,551 and PSS mean 20,47 (moderate stress level) with standard deviation 5,642. Bivariate result showed there was negative relationship between spirituality and stress (r= –0,267; p= 0,023). Conclusion: Therefore, holistic nursing care with spiritual approach can be done by nurse in education to elderly so they can enhance their spirituality as positive and effective stress management with more intense praying, increase holy scripture learning and social interaction with other people with positive religious practice and activity.